Distribusi Spasial Zona Rawan Kerusakan Gempa Berdasarkan Hasil Interpolasi Menggunakan Data Mikrotremor - Fadlan Arapah Bin Arifin; La Ode Restele; Jamal Harimudin; La Ode Hadini (Universitas Halu Oleo, 2024)
Earthquake is one of the disasters that can cause damage and losses to the affected communities. This research was conducted in the Moramo District hills, where an earthquake incident had occurred previously. The objectives of this study are to determine the characteristics of the region based on the parameters of earthquake damage vulnerability and to determine the spatial distribution of earthquake damage-prone zones based on interpolation results. The sample data consisted of microtremor data using the Quota Sampling method at 15 field measurement points and the shapefile of the Southeast Sulawesi Province. The data was processed using the Geopsy application and mapped using the IDW method by calculating the RMSE value to select the best interpolation result. The findings of this study are: The research area is generally vulnerable to damage caused by earthquakes, although the level of vulnerability tends to be low. There are three zones prone to earthquake damage: a low-damage zone covering almost the entire research area (eastern part of Pudaria Jaya, northern Wonua Jaya, western and southern Sumber Sari, and western Ulusena). A moderate-damage zone is located in the northern part of Watu Poramba, Wonua Jaya, and Sumber Sari, as well as western Ulusena. Meanwhile, a high-damage zone is found at T2, located in Pudaria Jaya Village.